LEARNING EFFICIENCY OF ELEMENTARY SCHOOL STUDENTS THROUGH E-LEARNING IN THE DISRUPTION ERA - Honest Ummi Kaltsum; Muh Jauhar Navis (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aims to 1. describe the implementation of learning efficiency of elementary school (SD) students through E-learning, 2. to know the advantages and disadvantages of its implementation. The research method used is descriptive qualitative with literature study design. The data collection technique was carried out by means of literature study in the form of academic manuscripts and from relevant previous research and from more than 20 scientific articles. The validity of the data was done by observing diligence. The data analysis technique used content analysis techniques. The results showed 1. The implementation of learning efficiency for elementary school students through e-learning was practical and effective with the support of the ease of technology and internet in teaching and learning activities between teachers and students. 2. The advantages of implementing the learning efficiency of elementary school students through e-learning in the era of disruption, namely between students and teachers with students easily sharing information, and saving costs, energy and time in getting maximum results, as well as students learning actively and independently. The drawback of implementing the learning efficiency of elementary school students through e-learning in the era of disruption is the lack of interaction between teachers and students, tends to ignore social and academic aspects, and not all places are available on the internet. The implication of this research is that teachers and students should be able to use e-learning wisely and the government should address the gap in internet access in Indonesia, especially in remote areas